Experimental Study on Strength of Concrete Partially Replacing Chiton shell as Fine Aggregate - Madhan Kumar, J; Kalaiselvan, R; raj, Raghul (International Journal of Engineering and Technology, 2018)
The most widely used material in the world is concrete, consequently there is a large requirement for raw material of concrete such as Fine Aggregate, Coarse Aggregate and cement. the huge extraction of the aggregate for manufacturing of concrete as serious effect on the environment due to depletion of natural resources and pollution. This affects the eco system to great extent. Hence the project deals with finding replacement for the existing raw material used in concrete by replacing the fine aggregate from river which is largely used in construction by chiton shell. Sea shell is the corpus of the marine organism. The sea shell has been grinded to 4.75mm and then replaced in the concrete. M20 mix was used and cubic specimen were casted for 5 different percentage of partial replacement as 0%, 5%, 10 %, 20%, and 25 %. All the specimens are tested for 7 & 28 days compressive, flexural and split tensile strength. it has been noted that the highest strength is obtained for 25% replacement of chiton shell. it was also observed thatÂ addition of sea shell power in concrete reduced workability hence superplasticizer were added to improve the consistency.Â